The Effects of Cinnamon on Newcastle Disease Performance and Hemato-Antibodies Titer in Broilers Iraq (Texas Journal of Agriculture and Biological Sciences, 2022)
This study will look into the effects of dietary cinnamon supplementation. Immunological serum tests are used to boost broiler immunity to the New Castle vaccine. Ross' flock consists of 308 one-day-old broiler chicks. T1 chicks received 2% cinnamon powder in their feed, T2 chicks received 4% cinnamon powder in their feed, and T3 chicks received 300 ppm cinnamon extract in their drinking water. Water and food must be provided for the duration of the thirty-day experiment. The first and second doses of the New Castle vaccine were administered to the birds. Titers of hem agglutination inhibition antibodies and antibody titers in an ELISA test were determined for these immunizations. Following the first and second vaccines, blood parameters such as the number of white blood cells and the heterophil/lymphocyt (H/L) ratio were also measured.